Improving Reading Comprehension Skills through the SQ3R Learning Method for Grade III Students at SDN No. 12 Pattene, Takalar Regency - Desy Ayu Andhira; Muhammad Saeful (Edumaspul: Jurnal Pendidikan, 2025)
This study aims to determine reading comprehension abilities through the SQ3R learning model in third-grade students at SDN No. 12 Pattene, Takalar Regency. The approach used is qualitative and quantitative, where each cycle is carried out in three meetings.The subjects in this study were 25 third-grade students at SDN No. 12 Pattene, Takalar Regency, consisting of 10 boys and 15 girls. The data collection technique used was documentation. The results of the study indicate that there was an improvement in reading comprehension skills among third-grade students at SDN No. 12 Pattene, Takalar Regency, using the SQ3R method. This was marked by an increase in the reading comprehension scores of students in cycle I from an average score of 69.6 to an average score of 86.24 in cycle II, or from a high category in cycle I to a very high category in cycle II.